EMANCIPAR A SUBJETIVIDADE: NOTAS SOBRE RECADO AO PARENTE, DE GUSTAVO CABOCO WAPICHANA (Muitas Vozes, 2024)
"Recado ao parente: fortificar nossos elos" (2020) is one of the works by Gustavo Caboco Wapichana, an indigenous multi-artist. As characteristic of the author's artistic endeavors, this piece is crafted using diverse languages - verbal, visual, and sonorous - and stands out for its poetic fertility and exploration of ethical, political, and vital themes pertaining to indigenous peoples' existence. One of the most thought-provoking aspects raised is the pressing need to cultivate unsubmissive and emancipated subjectivities. In essence, to exercise the vital power of creation (Rolnik, 2019), fostering subjective practices becomes imperative, with artistic and sensitive experiences emerging as particularly effective means for this purpose. Thus, to fully affirm life and avoid its numbing effects, the cultivation of affective-creative practices becomes indispensable, recognizing them as substantive nutrients to confront the "Colonial Coma" (Caboco, 2022).